2020
DOI: 10.1016/j.acra.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Drug-Eluting Bead Transarterial Chemoembolization Combined with Apatinib in Patients with Advanced Hepatocellular Carcinoma

Abstract: Rationale and Objective: The goal of this study was to determine the clinical efficacy and safety of drug-eluting bead (DEB) transarterial chemoembolization (TACE) in combination with apatinib administration in patients with advanced hepatocellular carcinoma (HCC). Materials and Methods: From December 2015 to May 2017, a total of 32 patients with advanced HCC treated with DEB-TACE combined with apatinib were consecutively enrolled in this study. The treatment response and laboratory outcomes were assessed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
4
11
1
Order By: Relevance
“…e efficacy of TACE combined with apatinib has been supported by several studies, whether the combination therapy of aTACE + apatinib is sufficient to achieve better therapeutic effects. Actually, compared with TACE plus apatinib, although the complications in this study are similar to those reported by Liu et al [30], aTACE combined with apatinib has more advantages in PFS (10.2 months vs. 9.5 months) and OS (23.3 months vs. 22.0 months) [31]. Moreover, the univariate Cox regression analysis indicated no considerable correlation between median PFS or median OS with age, Child-Pugh, cirrhosis, HBV infection, and AFP level.…”
Section: Discussionsupporting
confidence: 89%
“…e efficacy of TACE combined with apatinib has been supported by several studies, whether the combination therapy of aTACE + apatinib is sufficient to achieve better therapeutic effects. Actually, compared with TACE plus apatinib, although the complications in this study are similar to those reported by Liu et al [30], aTACE combined with apatinib has more advantages in PFS (10.2 months vs. 9.5 months) and OS (23.3 months vs. 22.0 months) [31]. Moreover, the univariate Cox regression analysis indicated no considerable correlation between median PFS or median OS with age, Child-Pugh, cirrhosis, HBV infection, and AFP level.…”
Section: Discussionsupporting
confidence: 89%
“… 21 Only one retrospective study has reported the efficacy of D-TACE-A for patients with HCC, and that study reported that the mOS, mPFS and DCR were 22 months (95% CI: 20.2–23.9), 9.5 months (95% CI: 8.1–10.9), and 90.6% in the third month after the initial therapy. 25 The mOS, mPFS, and DCR in that study were all higher than the mOS, mPFS, and DCR in the current one, possibly because the previous study included 18 patients (56.3%) with BCLC stage B, while the current study included 18 (18.8%) patients with BCLC stage B, who received D-TACE-A.…”
Section: Discussioncontrasting
confidence: 54%
“…Next, CalliSpheres Beads (Jiangsu Hengrui Medicine Co., Ltd., Jiangsu, China) with diameters of 300-500 µm loaded with 60 mg pirarubicin were infused via the microcatheter into the feeding arteries of the tumors. The loading procedure of CalliSpheres Beads-THP was performed similarly as the procedure described by Liu et al (2019). Finally, the feeding arteries were embolized with gelfoam particles until the stasis or near-stasis of the embolized vessel was achieved.…”
Section: Deb-bace Proceduresmentioning
confidence: 99%